Determinant factors in the international industry of printing and writing paper on a value chain perspective - Silva, Christian Luiz da (Review of Business Management, 2007)
The pulp and paper industry faces problems trying to match supply with demand, and that affects the decision-making process to be made in the several steps of the production chain. The need of increasing production creates high investment demands. However, the pressure towards low costs requires new investments in technologies, generally associated to process and product, cause the development of large corporations that are vulnerable to market and have low capability of affecting it. In order to understand such market dynamics and the factors determining its competitiveness, we should analyze how to aggregate value to this type of industry. The present study aims at analyzing the factors determining the international competitiveness of the printing and writing paper segment through an analysis comparing the Brazilian and international companies production chain. Preliminary, it was inferred that the main difference is set in the product distribution internationalization process that permits to innovate and participate in new market. Such internationalization process also allows the creation of new organization forms through cooperation within the production chain. The Brazilian companies should be more concerned about the way they are organized and sales of their products than about processes and products; they should be linked to an internationalization project which effectively provides the other country’s final consumer a guarantee that the Brazilian product has an aggregated value. Key-words: Competitiveness. Value chain. Printing and writing paper industry.